Sustainability Reporting, Green Accounting, Intellectual Capital, and Firm Size: Evidence on ROA in Basic Materials Sector (2021-2024) - Nur Athiyadina; Januar Eko Prasetyo (Politeknik Ganesha Medan, 2026)
This research aims to analyze the impact of sustainability reports, green accounting, intellectual capital, and firm size on company profitability with sales growth as control variable. The population in this study were basic materials sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. Profitability was measured using the Return on Assets (ROA) indicator as a proxy. The sampling technique employed in this research is purposive sampling, resulting in 69 sample observations that met the criteria. This study adopts a quantitative method with multiple linear regression analysis techniques through the Pooled Ordinary Least Squares (Pooled OLS) approach combined with year effect control. The data used in this research were obtained from secondary sources, including financial reports, sustainability reports, and PROPER ratings from companies listed on the Indonesia Stock Exchange (IDX) in the basic materials sector during the observation period. The empirical results of the analysis show that, sustainability report, green accounting, and firm size have no significant effect on profitability. In the other hand, intellectual capital is found to have a significant positive effect on profitability. This study contributes by combining GRI based sustainability disclosure and PROPER based environmental performance in a single model for a highly carbon-intensive sector. Findings imply that intangible assets dominates profitability, while sustainability disclosure, green accounting, and company size are not yet priced into accounting profitability in the short run.